Self-harm and substance use in a community sample of Black and White women with binge eating disorder or bulimia nervosa. - Dohm, F; Striegel-Moore, R; Wilfley, D; Pike, K; Hook, J; Fairburn, C (2002)
OBJECTIVE: This study evaluated rates of self-harm and substance use in women with either bulimia nervosa (BN) or binge eating disorder (BED) and assessed whether differences in self-harm and substance use are related to sexual or physical abuse. METHOD: Alcohol abuse, self-harm, and use or abuse of various illicit drugs were evaluated in a sample of 53 women with BN and 162 women with BED. RESULTS: Self-harm and substance use generally did not differentiate BED and BN cases, but rates of self-harm and substance use were elevated among women with a history of sexual or physical abuse relative to women without such a history. DISCUSSION: Elevated rates of self-harm and substance use may not be related uniquely to BN diagnostic status, but may be related to a characteristic shared by women with BN and BED, such as a history of sexual or physical abuse.